The Effect of Industry 4.0 Maturity on Company Performance in Manufacturing Companies - KARADEMİR, İLKER; OZGELDI, Murside (International Journal of Scientific Research and Management (IJSRM), 2022)
The business world is changing rapidly, business models, products, services, customer expectations and the market are affected by this change. Undoubtedly, the manufacturing industry is also affected by this rapid change in technology and industry. It is clear that companies need to adapt to the environment where this technology and digitalization are developing so rapidly. If the companies how better adapt to the Fourth Industrial Revolution (Industry 4.0), they will be permanent in this environment of uncertainty and they will gain a performance advantage over their competitors. In this study, the effect of Industry 4.0 maturity level of companies in the production sector in Turkey on firm performance was examined.